Architects' and interior designers' perspectives on hospital patient rooms designed by the people who work in these rooms. (September 2016) - Sommerich, Carolyn M.; Pires, Alex S.; Lavender, Steven A.; Sanders, Elizabeth B.-N.; Evans, Kevin D.; Li, Jing; Patterson, Emily
Increasing interest in acuity-adaptable patient rooms, performing more services in patient rooms, and the increasing size of the population all have implications for the patient room as a workspace, including the number of people working in the room, types of tasks performed, and amount and layout of the space in which tasks are performed. This presentation describes an analysis of the opinions of professionals who typically control the design of hospital patient rooms, concerning five med/surg patient room designs developed through a participatory process involving mixed groups of hospital staff members, all of whom work in patient rooms. Ratings and comments provided by the design professionals identified clear preferences for one of the designs, as well as rooms and design elements for which there were more mixed or negative opinions. It is important for architects and designers to understand how room size, layout, and organization of features can be used to facilitate work for the full spectrum of hospital staff members who work in patient rooms. Such facilitation can reduce physical strain and improve efficiency and patient care.